JOKOWI MEMBANGUN SOLO: STUDI KASUS ATAS GAYA KEPEMIMPINAN WALIKOTA SOLO DALAM PROSES RELOKASI PEDAGANG KAKI LIMA MONUMEN ’45 BANJARSARI, SURAKARTA - Dyah Ratri Ismi Hayuningtyas; Helly P. Soetjipto; Sri Respati Andamari (Universitas Sarjanawiyata Tamansiswa, 2013)
ABSTRACT Implementation of relocation of street vendors (PKL) has now become the spotlight of public attention. Frequent clashes in various cities in Indonesia between government officials are generally represented by the Pramong Satuan Polisi Praja (Satpol PP) with street vendors. However, this did not happen in Solo, Central Java during the reign of Governor Joko Widodo in 2006. This study aims to find an answer to how Joko Widodo's leadership style (also known as Jokowi) as Mayor of Surakarta to approach the street vendors In Monument '45 Banjarsari Surakarta so they can move without risk or resistance effectively. To understand the concept of leadership style used in the relocation process done by Jokowi in Solo, the researcher conducted a qualitative analysis to develop typology and found five main interpretations of his leadership style from the point of view of street vendors. Leadership style is: populist, sembodo (consistent), nguwongke (appreciate), ngemong (care) and visionary. The results show that street vendors with a background in Solo need a psychological and cultural approach to conduct relocation without resistance. Keywords: street vendors, relocation, leadership style, cultural influences